Tsunami Vulnerability Analysis Based on Coastal Typology in the Coastal Area of Ende City - Maria Theresia Firmina Baru; Djati Mardiatno; Muh Aris Marfai (JURNAL GEOGRAFI, 2024)
A tsunami disaster threatens Ende City. Ende City's coastal area management policy regarding disaster mitigation must consider coastal typology. Efforts to reduce the risk of tsunamis must pay attention to the physical development of coastal land to maintain the coastal resources. Therefore, this research aimed to analyze the level of tsunami susceptibility based on coastal typology in the coastal area of Ende City. The methods used in this research are survey and spatial analysis. The survey results were compared with literature studies to determine coastal typology and land use. Spatial analysis uses overlay, scoring, and weighting techniques to produce tsunami susceptibility levels. Geospatial parameters that determine the level of susceptibility are topography, distance from the coastline, slope, distance from rivers, and coastal morphology. Susceptibility analysis is carried out for each coastal typology because each has a different response to tsunami. The research results show five classes of tsunami susceptibility: very susceptibility, susceptibility, somewhat susceptibility, safe, and very safe. Very susceptible areas are marine deposition coast typology, anthropogenic coast typology, and sub-area deposition coast typology. The secure areas are wave erosion coast typology and volcanic coast typology.Keywords: Coastal City of Ende, Coastal Typology, Tsunami, Susceptibility, Land Use.